Respuesta :
Answer:
Part A : k = k₁+k₂
Part B: k = k₁+k₂+.....kₙk₃
Where for 3 springs n= 3
Explanation:
Hooke's law states that the force required to stretch a spring is directly proportional to the distance x, where k is the spring constant.
Mathematically, Hooke's law is represented as
F = kx
Where F = Force required to stretch the spring
k = spring constant
x = distance
Part A:
Since the two massless springs in Part A are connected in parallel, it means they are stretched by the same Force (F)
Therefore using Hooke's law
F = kx ......... Equation 1
Total Force is represented by F
Spring 1 , F₁= k₁x ....... Equation 2
Spring 2, F₂= k₂x ......... Equation 3
Total Force = F₁ + F₂ .......... Equation 4
We substitute k₁x for F₁ and k₂x for F₂ in equation 4
F= k₁x+k₂x ........ Equation 5
F = (k₁+k₂)x ........ Equation 6
According to Hooke's law, F = kx
We substitute kx for F in Equation 6
Hence, kx = (k₁+k₂)x ........... Equation 7
Therefore, the Effective springs constant for two massless spring connected in parallel is given as
k = k₁+k₂
A) The effective spring constant in terms of k₁ and k₂ is; k = 1/[(1/k₁) + (1/k₂)]
B) The effective spring constant in terms of k₁, k₂ and k₃ is; k = 1/[(1/k₁) + (1/k₂) + (1/k₃)]
A) We are told that springs 1 and 2 have spring constant as k₁ and k₂ respectively.
Now, formula for force on a spring is;
F = kx (the negative sign was ignored because it only shows that the force of restoration acts in an opposite direction to the applied force)
Where;
F is force
k is spring constant
x is extension of spring.
Thus;
F1 = k₁•x₁
F2 = k₂•x₂
Now, we are told that the springs are extended by the same amount.
Thus, total extension;
x_eq = x₁ + x₂
Since a constant force is being exerted on the rod, then from F = kx, we have;
F/k = F₁/k₁ + F₂/k₂
However, F₁ = F₂ = F since we are told that the same force acts on the rod. Thus;
F/k = F/k₁ + F/k₂
F will cancel out to give;
1/k = (1/k₁) + (1/k₂)
k = 1/[(1/k₁) + (1/k₂)]
B) We are told that there is now a third spring connected in parallel with the other 2 springs.
Just like in answer A above, force on the third spring will be;
F₃ = k₃x₃
Since the force is constant throughout, it means it's the same as for the other 2 springs in the system. Thus;
F/k = F/k₁ + F/k₂ + F/k₃
F will cancel out to give;
1/k = (1/k₁) + (1/k₂) + (1/k₃)
We want to make k this subject of the formula. Thus;
k = 1/[(1/k₁) + (1/k₂) + (1/k₃)]
Read more at; https://brainly.com/question/13608225